BIOMARKERS AND PROGNOSTIC SCORING IN CEREBRAL MALARIA - Orlando Pikatan; Ellen Ferlita Tirtana; Kezia Seraphine; Wienta Diarsvitri (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Malaria remains a public health concern and remain the deadliest in infectious disease in the world. Cerebral malaria is a particularly severe complication of this disease and associated with high mortality. This literature review is made up from 19 literatures consisting of journals, and book. The literature review used data base www.pubmed.com, and www.scholar.google.com using “cerebral malaria and biomarker, predictor of cerebral malaria and treatment of severe malaria”. The languages for this journal are English and Indonesian. From the collection of literatures in this literature review, severe consists of cerebral malaria, blackwater fever, acute kidney injury, pulmonary edema, electrolyte disturbance, hematology disturbance, and obstetrics emergency resulting from malaria which is postpartum hemorrhage. Cerebral malaria increases the mortality of the patient, so they have to be diagnosed early and treated precisely. Patients with infection of plasmodium falciparum and GCS<11 must be suspected as cerebral malaria. Biomarker examination such as Soluble ICAM-1, Specific muscle’s protein, Angiopoetin-1 and 2, and Plasma microparticles is the most precise way to detect malarial emergency earlier Coma Acidosis Malaria score is also found to be useful in predicting the prognosis in cerebral malaria. Early diagnosis should be made as early as possible to reduce mortality from malaria and its emergencies.